Effectiveness of Intrumental music therapy to decrease of stress levels in student level study end nursing university sahid Surakarta - Ahmad Syamsul Bahri; Idris Yani Pamungkas (Jurnal Ilmu Keperawatan Indonesia (JIKI), 2017)
.